OC-009 A Multicentre Retrospective Comparison Of Plastic, Uncovered And Fully Covered Metal Stents In The Management Of Distal Malignant Biliary Strictures. (9th June 2014) - Elias, JE; Sampaziotis, F; Griffiths, WJ; King, AL; Macfarlane, B; Woodward, JM; Corbett, GD; Leahy, A
Abstract : Introduction: Uncovered self-expanding metal stents (USEMS) remain patent longer than plastic stents (PS) in patients with malignant bile duct strictures (MBDS). However, their difficult removal can compromise surgical tumour resection and so, prior to tumour staging a PS is commonly used. A solution may be offered by metal stents which have been coated with plastic, making them easier to remove. Our preliminary data analysis [1] suggested that fully covered self-expanding metal stents (FCSEMS) used as first line management of MBDS result in a longer patency time and similar complication rates compared to USEMS and PS. We now present data from an expanded database of patients to provide further evidence of the efficacy of FCSEMS in this situation. Methods: A multicentre retrospective study was conducted of patients with MBDS who underwent ERCP and primary stenting with PS, USEMS or FCSEMS between 2007 and 2013. Data was collected from patient records on age, cancer type, stent patency time, complications and survival. Patency time was calculated as the period between stent insertion and occlusion, death or resection with a patent stent. Patients who underwent resection were excluded from the patient survival analysis. Statistical analysis used Kaplan Meier and Log Rank tests for patency and survival and Fisher's exact test for complications. The software used was IBM SPSS Statistics 20. Results: 268 patients were included. FCSEMS (n = 41) remained patent for a mean of 292 days versus 150 days for USEMS (n = 89) (p < 0.001) and 68 days for PS (n = 138) (p < 0.001). FCSEMS also resulted in a statistically significant improvement in patient survival with a mean of 297 days versus 191 days for USEMS (p < 0.001) and 216 days for PS (p = 0.001). Both FCSEMS and USEMS produced a significantly lower incidence of cholangitis than PS (p < 0.047 and <0.013 respectively). There were 2 episodes of pancreatitis in the FCSEMS group (4.9%) compared to 3 in the PS group (2.2%) and 1 in the USEMS group (1.1%) but this was not statistically significant. Conclusion: For primary stenting of MBDS, FCSEMS result in a longer patency time and a reduced incidence of cholangitis compared to PS. Combined with evidence supporting their ease of operative removal, this data suggests FCSEMS may be the superior option for primary stenting of MBDS. However, a larger cohort will be required to clarify the significance of the increased risk of pancreatitis observed in the FCSEMS group. Reference: 1 Sampaziotis et al . A retrospective comparison of plastic, uncovered and fully covered metal stents in the management of distal malignant biliary strictures. BSG Abstract 13–1209 Disclosure of Interest: None Declared.